Validation of an Automated Cough Detection Algorithm for Tracking Recovery of Pulmonary Tuberculosis Patients - Larson, S (2012)
This work was funded in part by National Institutes of Health through awards 5D43TW006581 "Infectious Diseases Training Program in Peru'' and R21 AI094143 "Cough-A Rapid Indication of Response to Therapy in Pulmonary Tuberculosis''. JL and MB were supported by NIH Fogarty Foundation fellowships. G. Comina wants to thank the Consejo Nacional de Ciencia, Tecnologia e Innovacion Tecnologica of Peru (CONCYTEC) for their support. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.